Exploring the Potentials of Using Smartphones in Enhancing Learning English at the University - Mustapha Boudjelal (Journal of English Teaching, 2022)
This article investigates the pedagogical benefits of smartphones as a form of mobile learning in English language classes. This study which stems from the experience of the author as a teacher of English at the university seeks two main aims: shedding light on learners’ perceptions and awareness of the pedagogical usages of smartphones and exploring learners’ usages of cellphones inside and outside the classroom settings. To rigorously explore the afore-mentioned aims, a survey questionnaire had been administered to 18 Master students of English Didactics and Applied Languages, Mostaganem University). The analysis of the collected data revealed that the use of smartphones for pedagogical purposes is obstructed by various hindrances that emanate from learners’ unawareness of their academic usages and teachers’ negative attitudes towards them.